Histocompatibility HLA system of man. Consideration in the light of current concepts. I. Organization and polymorphism - Kedzierska, A; Turowski, G (Przeglad lekarski, 2001)
The HLA system, which represents the major histocompatibility complex (MHC) of man, encompasses approximately one thousandth of the human genome and is localised on the short arm of chromosome 6 (band 6p 21.3). The HLA gene complex shows an extreme polymorphism which can be demonstrated by molecular genetic methods. The genes so far recognised in the HLA can be subdivided into three major classes: 1) the HLA class I (HLA-ABC) and class II genes (HLA-D); 2) immune function related genes (C2, C4A, C4B, TNFA and TNFB, transporter and proteasome genes); 3) other genes apparently not related to immune functions (CYP 21, valyl-tRNA synthetase). The loci HLA-A, -B, and -C represent the classical HLA class I loci with gene products expressed on nearly all nucleated cells; HLA-E, -F and -G the non-classical HLA class I loci, code for products with a limited tissue distribution and a restricted polymorphism. Classical class I and II MHC antigens are integral membrane proteins composed of two pairs of structurally similar extracellular domains. The X-ray studies indicated the presence of peptides bound to HLA molecules within the groove. The groove has on its floor several amino acids where peptides, derived from the antigen being presented, are bound. Although the principle of allele specific motives ruling the peptide binding seems to be become more established, the further biological impact of the allelic variation remains subject for future studies.